2005
DOI: 10.1093/rpd/nci337
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose to family members of hyperthyroidism and thyroid cancer patients treated with 131I

Abstract: The thermoluminescence dosemeter (TLD) was used for measuring radiation dose to family members of thyrotoxicosis and thyroid cancer patients treated with (131)I using CaSO(4):Dy discs. There were 45 family members of thyrotoxicosis patients, who were divided into two groups with 22 in the first and 23 in the second group. Radiation safety instructions were the same for both the groups except in the second group where the patients were advised to use a separate bed at home for the first 3 d of dose administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 10 publications
1
27
0
1
Order By: Relevance
“…Pant et al [8] measured the radiation dose using TLD badges until 15 days after the release of patients and reported that only 1 of 342 family members were exposed to more than 5 mSv, even though those family members cared for the patients in an isolation room and after discharge to home. The one who received more than 5 mSv (8.5 mSv) was a close relative of the patient who was disabled and unable to move.…”
Section: Discussionmentioning
confidence: 99%
“…Pant et al [8] measured the radiation dose using TLD badges until 15 days after the release of patients and reported that only 1 of 342 family members were exposed to more than 5 mSv, even though those family members cared for the patients in an isolation room and after discharge to home. The one who received more than 5 mSv (8.5 mSv) was a close relative of the patient who was disabled and unable to move.…”
Section: Discussionmentioning
confidence: 99%
“…These are very consistent and reasonable results, because the patients were expected to show good compliance with radiation safety instructions. However, in a more large-scale study, there were some exceptional cases in which the exposures were over 1 mSv, although the usual radiation exposure was less than 1 mSv [11]. In the study, especially in the groups that used mass transport for the trip back home, 22-27% of family members showed radiation exposure of over 1 mSv.…”
Section: Discussionmentioning
confidence: 81%
“…Since the revision of the US NRC Regulatory Guide, several studies have reported that patients' release is safe for their family members, even with high-dose RIT using 3.7-5.6 GBq of 131 I [6][7][8][9][10][11]. These results are very consistent and reasonable.…”
Section: Introductionmentioning
confidence: 69%
“…Exposed TLDs were read with a Harshaw 6600 TLD reader. The equivalent doses were expressed in microsieverts or millisieverts, after corrected for background, by use of the dose-response (calibration) curves for 99m Tc and 131 I gamma rays (8). The radiation weighting factor for the gamma photons from both 131 I and 99m Tc was taken as 1.…”
Section: Methodsmentioning
confidence: 99%